Effectiveness, safety and feasibility of extended‐release naltrexone for opioid dependence: a 9‐month follow‐up to a 3‐month randomized trial. (22nd June 2018) - Solli, Kristin Klemmetsby; Latif, Zill‐e‐Huma; Opheim, Arild; Krajci, Peter; Sharma‐Haase, Kamni; Benth, Jūratė Šaltytė; Tanum, Lars; Kunoe, Nikolaj
Abstract: Background and aim: This is a follow‐up study of a previously published randomized clinical trial conducted in Norway that compared extended‐release naltrexone (XR‐NTX) to buprenorphine–naloxone (BP‐NLX) over 3 months. At the conclusion of the trial, participants were offered their choice of study medication for an additional 9 months. While BP‐NLX was available at no cost through opioid maintenance treatment programmes, XR‐NTX was available only through study participation, accounting for why almost all participants chose XR‐NTX in the follow‐up. The aim of this follow‐up study was to compare differences in outcome between adults with opioid dependence continuing XR‐NTX and those inducted on XR‐NTX for a 9‐month period, on measures of effectiveness, safety and feasibility. Design: In this prospective cohort study, participants were either continuing XR‐NTX, changed from BP‐NLX to XR‐NTX or re‐included into the study and inducted on XR‐NTX treatment. Setting: Five urban, out‐patient addiction clinics in Norway. Participants: Opioid‐dependent adults continuing ( n  = 54) or inducted on ( n  = 63) XR‐NTX. Intervention: XR‐NTX administrated as intramuscular injections (380 mg) every fourth week. Measurements: Data on retention, use of heroin and other illicit substances, opioid craving, treatment satisfaction, addiction‐related problems and adverse events were reported every fourth week. Findings: Nine‐month follow‐up completion rates were 51.9% among participants continuing XR‐NTX in the follow‐up and 47.6% among those inducted on XR‐NTX. Opioid abstinence rates were, respectively, 53.7 and 44.4%. No significant group differences were found in use of heroin and other opioids. Conclusions: Opioid‐dependent individuals who elect to switch from buprenorphine–naltrexone treatment after 3 months to extended‐release naltrexone treatment for 9 months appear to experience similar treatment completion and abstinence rates and similar adverse event profiles to individuals who had been on extended‐release naltrexone from the start of treatment.